SUSTAINABLE DEVELOPMENT: GOAL, TASKS, CONDITIONS, CONCEPT - Schneider, O.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Modern conditions of economic relations have determined the role of sustainable development for business entities as the highest priority. Currently, sustainable development is an important and primary goal for any successful business entity, since achieving high financial results in this state of the business is no longer enough to attract investors and satisfy the interests of key stakeholders. In this regard, the issue of the development and application of the concept of sustainable development by Russian business entities of various industries and fields is becoming increasingly important. However, it should be noted that today only large Russian companies operating in the country, as well as abroad, pay attention to this issue and implement the concept of sustainable development. The wide scope of activities and work in international markets obliges such companies to take into account issues relating not only to the financial sector, but also to the environmental and social component, since for the world community the last two components of sustainable development are more important. In fact, the concept of sustainable development of a company is a set of goals, objectives, principles in the field of sustainable development of a business entity, as well as a set of methods and tools for evaluating activities to achieve sustainable development goals.